Case report: Pain in anti-DPPX encephalitis - Bjerknes, Tale L.; Steihaug, Ole Martin; Haugen, Mette; Hjelland, Ina Elen; Vedeler, Christian Alexander (Frontiers in Neurology, 2022)
Encephalitis due to antibodies targeting dipeptidyl-peptidase-like protein 6 (DPPX), a potassium channel subunit, is rare. The illness is typically characterized by a triad of weight loss, CNS hyperexcitability and cognitive symptoms, but recent reports suggest that the clinical picture may be more heterogeneous. Here, we describe the case of a 63-year-old female who was admitted to the hospital with severe extremity pain, which had been preceded by diarrhea and weight loss. She later developed cognitive changes, and her general condition rapidly deteriorated. Extensive workup did not reveal gastrointestinal illness or underlying malignancies. MRI of the brain was normal. Analyses of blood and cerebrospinal fluid showed normal cell counts but high titres of DPPX antibodies in blood and cerebrospinal fluid. The patient was treated with intravenous methylprednisolone followed by rituximab. At 1-year follow-up, she was without pain and had completely recovered. In this case, DPPX-associated autoimmune encephalitis was dominated by severe extremity pain, illustrating that sensory symptoms may be one of the main complaints in these patients. It is important for clinicians to be aware of the heterogeneous clinical picture in this serious condition, since correct diagnosis and treatment with immunosuppressants are associated with favorable prognosis.